Analysis of Life Satisfaction of the Elderly based on Sports Activities - Sufyar Mudjianto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Most elderly people in Indonesia experience physical and psychological health problems, with the percentage of those who are sick around 48.14%. Health problems, low income, and difficulties in daily activities are some of the factors that can influence their life satisfaction. The aim of this research is to analyze the life satisfaction of elderly people based on the sports activities they participate in, namely gateball, golf, gymnastics, fitness activities, and tennis. The research method used by researchers is the explanatory survey or descriptive survey method. An explanatory survey is a type of survey that is useful in comparing variables by testing hypotheses and samples obtained from a population. The subjects and locations that will be studied by researchers are the sports community of elderly people in the city of Bandung. As many as 74 respondents are active members of the sports community of elderly people in Bandung City. The results of the analysis show that there are differences in parents' life satisfaction based on the sport they do. The average score of respondents who played golf showed the highest life satisfaction. then tennis, aerobics, fitness sports, and gateball. Physical activity for older people is good for health and quality of life; therefore, exercise programs for older adults should focus on maintaining functional capacity and quality of life with lower intensity, frequency, and duration.